Evaluation And Modeling of Business Processes in Employee Admissions Selection Using The Quality Evaluation Framework (Qef) Case Study (PT. Indofresh) - Andrianto, Eko; Firmansyah , Gerry (The Islamic Education and Multiculturalism Foundation, 2023)
This study aims to simplify business processes to increase the effectiveness and efficiency of a recruitment process and improve the performance of the recruitment business process. In this study, the authors used descriptive research with a qualitative approach. The conceptual framework model in this research consists of problems, methods, comparative experiments, and results, so the research procedure also needs to be carried out because it is wrong one crucial process, from the results of the analysis using the Quality Evaluation Factor (QEF) researchers found that there were findings of four quality factors that did not match the target of the employee recruitment process in PT. Indofresh is the business process of receiving application files and screening application files, invitation business processes, business processes of candidates present in the test and psychological test process, and business processes of participants to continue the interview process. Of the four quality factors, researchers identified the causes of discrepancies in the recruitment process in observations and interviews conducted and used them as a basis for improvements to the corresponding kids. Modeling carried out using BPMN is then simulated to get several recommendation results on each quality factor.